Study of clinical profile of tuberculosis patients admitted in respiratory medicine ward at a tertiary care hospital in Marathwada - B. Bilagi, Rakesh; Deshmukh, Hafiz (International Journal of Advances in Medicine, 2018)
Background: Tuberculosis is one of the most important cause of most of the respiratory diseases. It is estimated that about one-third of the world's population is infected with mycobacterium tuberculosis. It is important to know about the clinical profile of these patients. There are many studies which are done among OPD patients but fewer among indoor patients hence, the current study was planned. Methods: Retrospective study of the patients admitted in the inpatient department of the study area were taken as the sample size from May 2016 to April 2017, who were diagnosed as TB patients. Results: a retrospective study was conducted among admitted patients, which included data of one year. There was male predominance with male: female ratio of 2.89. major cause of admission was extrapulmonary causes. The HIV patients were more predisposed to extrapulmonary and diabetes than pulmonary tuberculosis. Conclusions: There is male predominance for admission cases. There is also increased cases of extrapulmonary TB admitted than pulmonary cases.